Randomised Controlled Trial on Prophylaxis of Mastitis–Metritis–Agalactia Syndrome in Swine using Caulophyllum Logoplex and Lachesis Logoplex - Büttner, Kathrin; Oelkers, Janna; Burfeind, Onno; Krieter, Joachim; Czycholl, Irena (Homeopathy, 2023)
Background Mastitis–metritis–agalactia (MMA) syndrome occurs in the first days post-partum and causes piglet losses mainly due to malnutrition. One possibility for prophylaxis of MMA is via homeopathy. In this veterinary study, the effectiveness of a prophylactic administration of homeopathic remedies for the prevention of the occurrence of MMA in swine was evaluated.Methods In a randomised and blinded study, 60 sows were examined. Sows were randomly distributed in two groups: the experimental group (CL/LL) received a prophylactic administration of the complex homeopathic remedies Caulophyllum Logoplex and Lachesis Logoplex, and the placebo group was administered a sodium chloride (NaCl) solution in the same injection scheme as the experimental group. Clinical signs of MMA, behavioural changes, as well as production parameters, were recorded beginning with the day of farrowing until 5 days post-partum.Results The treatment group showed no significant effect on the occurrence of MMA in sows (CL/LL: 56.67% MMA positive sows; NaCl: 53.53% MMA positive sows). Treatment group had also no significant effect on health parameters (vaginal discharge, raised rectal temperature, shortage of milk) or behavioural parameters (impaired feeding behaviour and impaired general condition). For the production parameter average weight gain, statistically significant effects in the treatment group were detected.Conclusions Prophylaxis with the homeopathic remedies Caulophyllum Logoplex and Lachesis Logoplex showed neither an improvement in MMA prevention nor an improvement in health parameters or behavioural traits in the present herd of sows.
Keywords: sows; piglets; homeopathic prophylaxis; mastitis–metritis–agalactia syndrome